Strategi Guru dalam Meningkatkan Minat Belajar Peserta Didik di MI Raudlatul Ulum - Hauliyah, Hikayatul; Habibie, Naufal; Hidayat, Imam Nurul; Araisy, Frayoga Maulana; Kurnia, Lisa (ANWARUL, 2022)
In the context of the interaction of the learning process, students experience a tendency to be less motivated in learning. This study reveals efforts to increase students' interest in learning, and student learning activities, the ability of teachers to provide learning motivation and also student learning responses through class lessons. This study aims to increase students' interest in learning, determine student learning activities, teacher's ability to provide interest in learning, and also determine student learning responses through classroom learning. Various strategies that can be applied by teachers through classroom learning so that students are interested in learning. However, teachers are required to have creativity and innovation in creating a conducive and effective learning atmosphere.